The effects of rest breaking agents, pruning and evaporative cooling on budbreak, flower bud formation and yield of three pistachio (Pistacia Vera L.) cultivars in a climate with moderate winter chilling - Muller, Anton Michael (Stellenbosch : Stellenbosch University, 2012)
Thesis (MScAgric)--Stellenbosch University, 2008.